Memorandum of Understanding between the International Livestock Research Institute (ILRI) and Debre Markos University - International Livestock Research Institute; Debre Markos University (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Memorandum of understanding (MoU) between the International Livestock Research Institute (ILRI) and Debre Markos University. On March 30, 2022, MoU was signed by Jimmy Smith, Director-General of ILRI, and Tafere Melaku, President of Debre Markos University.